DEVELOPMENT OF COAXIAL ROTOR MICRO UNMANNED AERIAL VEHICLE - H. P Thien; T Mulyanto; H Muhammad; S Suzuki (Mesin, 2009)
Micro Unmanned Helicopter with ability of takeoff, landing and hovering offeres excellent support tool for missions in indoor environment. In this paper, a review of preliminary studies towards the development of autonomous coaxial helicopter MAV is presented. The paper starts with the statement of coaxial helicoper MAV development. Then, it is continued by the introduction of development of dynamic model for a typical coaxial rotor platform. In the third issues, initial steps in development of sensory system and control system will be dealt with. In brief, an analytical mathematical model has successful derived. This model together with the developed sensor system will act important role towards the full development of the dynamics model as the system identification is carried out.